Recent Developments in South African Consumer Insolvency Law - An analysis of the National Credit Amendment Act 7 of 2019 and its possible impact on the economy, taking into account the experiences of the British, New Zealand and German legal systems - Bär, Alida Lucia (Department of Public Law, 2020)
A key challenge of the present is the growing number of consumer debtors, often caused by easy access to credit. Especially for people on low incomes, even an unforeseen event can lead to a situation in which credit rates can no longer be serviced. The result is insolvency. However, in the past many jurisdictions were not prepared for the challenges of low income insolvency. It was not until more recent times that legislators began to develop special insolvency procedures tailored to people with low incomes. This comparative research presents the insolvency proceedings of South Africa, in particular the recently introduced low income insolvency proceedings, and compares them with those of New Zealand, Great Britain and Germany, whereby Germany is the only one of these countries without a low-income insolvency procedure. It is established that each of these proceedings has advantages and disadvantages. It is also noted that despite the existence of insolvency proceedings, the number of consumer debtors continues to rise. Therefore, in addition to a proposal for insolvency proceedings combining the feasible aspects of each of the legal systems presented, it is also proposed to teach financial literacy at school in order to prevent over-indebtedness.